Software process improvement and capability determination : 16th International Conference, SPICE 2016, Dublin, Ireland, June 9-10, 2016, Proceedings /: 16th International Conference, SPICE 2016, Dublin, Ireland, June 9-10, 2016, Proceedings. (2016) - Unknown
No abstract available